High Step-up DC-DC Converter Using Voltage Lift Techniques for Renewable Applications - Saed Mahmoud Alilou; Mohammad Maalandish; Ataollah Samadian; Pouya Abolhassani; Seyed Hossein Hosseini; Mohammad-Hassan Khooban (CSEE Journal of Power and Energy Systems)
This paper presents a non-isolated DC-DC boost converter using voltage lift techniques. The proposed structure offers continuous input current. Substantial voltage gain along-side low voltage stress across semiconductors in this topology contribute to utilizing an MOSFET with lower <tex>$R_{\text{DS-ON}}$</tex> and devices with low nominal voltage values. Consisting of a switch makes the control procedure of the converter uncomplicated. Voltage analysis for the converter has been done in continuous and discontinuous conduction modes (CCM)-(DCM). Furthermore, current calculation, design process and comparison study are provided. Dynamic performance of the proposed circuit is scrutinized by applying the state space average technique and small signal model. In order to accredit performance of the converter, an archetype with 26V input and 222V output voltages and approximately 196W power level at 50 kHz switching frequency has been built and tested.